2011
DOI: 10.1310/sci1603-84
|View full text |Cite
|
Sign up to set email alerts
|

YouTube as an On-line Disability Self-Management Tool in Persons With Spinal Cord Injury

Abstract: On-line knowledge sharing of disability self-management offers a learning advantage in that it can be individualized to on-line community members' needs. It also promotes accessibility by removing the geographic, transportation, financial, time, and distance barriers that often accompany face-to-face, patientoriented education. A consumer-focused training project conducted at the Rehabilitation Research and Training Center on Spinal Cord Injury aims to promote self-management skills in persons with SCI in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 4 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…YouTube videos related to the chronic cerebrospinal venous insufficiency "liberation" procedure (Mazanderani, O'Neill, & Powell, 2013). (Libin et al, 2011).…”
Section: Community Was Evidenced Through Posts and Comments Onmentioning
confidence: 99%
“…YouTube videos related to the chronic cerebrospinal venous insufficiency "liberation" procedure (Mazanderani, O'Neill, & Powell, 2013). (Libin et al, 2011).…”
Section: Community Was Evidenced Through Posts and Comments Onmentioning
confidence: 99%
“…Similar results were produced by a 2014 survey of 500 veterans with SCI [19]. For those with internet access, educational videos addressing management of SCI secondary conditions (eg, managing or preventing pressure ulcers or pain) have increased health-management knowledge and encouraged behavior changes (eg, the adoption of hypnosis) [20,21]. E-learning modules on topics such as pressure ulcer or bladder management have been linked to increased management knowledge [22][23][24] and internet usage has generally been associated with emotional health [25,26].…”
Section: Virtual Self-management Supportmentioning
confidence: 63%
“…However, the online health information landscape is quickly changing; more recent studies of forum discussions of care for HIV, for example, have found information posted by online users to be of "good quality" when evaluated by medical professionals [45]. Trustworthy sources of information about SCI are, moreover, increasingly available online (eg, [20][21][22]46]).…”
Section: Principal Findingsmentioning
confidence: 99%
“…Similar results were produced by a 2014 survey of 500 veterans with SCI [ 19 ]. For those with internet access, educational videos addressing management of SCI secondary conditions (eg, managing or preventing pressure ulcers or pain) have increased health-management knowledge and encouraged behavior changes (eg, the adoption of hypnosis) [ 20 , 21 ]. E-learning modules on topics such as pressure ulcer or bladder management have been linked to increased management knowledge [ 22 - 24 ] and internet usage has generally been associated with emotional health [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%